Regional contributions of six preventable risk factors to achieving the 25 × 25 non-communicable disease mortality reduction target: a modelling study. Issue 12 (December 2015) - Kontis, Vasilis; Mathers, Colin D; Bonita, Ruth; Stevens, Gretchen A; Rehm, Jürgen; Shield, Kevin D; Riley, Leanne M; Poznyak, Vladimir; Jabbour, Samer; Garg, Renu Madanlal; Hennis, Anselm; Fouad, Heba M; et al.
Summary: Background: Countries have agreed to reduce premature mortality from the four main non-communicable diseases (NCDs) by 25% from 2010 levels by 2025 (referred to as the 25 × 25 target). Countries also agreed on a set of global voluntary targets for selected NCD risk factors. Previous analyses have shown that achieving the risk factor targets can contribute substantially towards meeting the 25 × 25 mortality target at the global level. We estimated the contribution of achieving six of the globally agreed risk factor targets towards meeting the 25 × 25 mortality target by region. Methods: We estimated the effect of achieving the targets for six risk factors (tobacco and alcohol use, salt intake, obesity, and raised blood pressure and glucose) on NCD mortality between 2010 and 2025. Our methods accounted for multicausality of NCDs and for the fact that, when risk factor exposure increases or decreases, the harmful or beneficial effects on NCDs accumulate gradually. We used data for risk factor and mortality trends from systematic analyses of available country data. Relative risks for the effects of individual and multiple risks, and for change in risk after decreases or increases in exposure, were from reanalyses and meta-analyses of epidemiological studies. Findings: The probability of dying between the ages 30 years and 70 years from the four main NCDs in 2010 ranged from 19% in the region of the Americas to 29% in southeast Asia for men, and from 13% in Europe to 21% in southeast Asia for women. If current trends continue, the probability of dying prematurely from the four main NCDs is projected to increase in the African region but decrease in the other five regions. If the risk factor targets are achieved, the 25 × 25 target will be surpassed in Europe in both men and women, and will be achieved in women (and almost achieved in men) in the western Pacific; the regions of the Americas, the eastern Mediterranean, and southeast Asia will approach the target; and the rising trend in Africa will be reversed. In most regions, a more ambitious approach to tobacco control (50% reduction relative to 2010 instead of the agreed 30%) will contribute the most to reducing premature NCD mortality among men, followed by addressing raised blood pressure and the agreed tobacco target. For women, the highest contributing risk factor towards the premature NCD mortality target will be raised blood pressure in every region except Europe and the Americas, where the ambitious (but not agreed) tobacco reduction would have the largest benefit. Interpretation: No WHO region will meet the 25 × 25 premature mortality target if current mortality trends continue. Achieving the agreed targets for the six risk factors will allow some regions to meet the 25 × 25 target and others to approach it. Meeting the 25 × 25 target in Africa needs other interventions, including those addressing infection-related cancers and cardiovascular disease. Funding: UK Medical Research Council.